ZIF-8 deposited onto TiO2 microcolumns as effective catalyst for CO2 reduction. - Romero Guerrero, Juan Jesús; Pedrosa Poyato, José María (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2022)
Motivation:.Global warming is one of the biggest issues that society is currently facing. CO2 is one of the most important gases of greenhouse gases due to anthropogenic emissions from industrial activities, transport, energy sector, agriculture, livestock, etc. An environmentally friendly alternative to reduce the amount of CO2 is the use of Metal-Organic Frameworks (MOFs), in particular, a subfamily of MOFs that is isoreticular to zeolites namely Zeolitic Imidazolate Framewor (ZIFs). These compounds have shown in prevous works electrocatalytic activity for CO2 reduction Methods: In order to carry out this application, ZIF-8 is chosen for its excellent thermal and chemical stability. For this purpose, it is necessary to deposit the compound onto a conductive substrate, in this case, FTO. ZIF-8 was grown in situ on TiO2 microcolumns that were previously deposited on the FTO substrate by chemical vapour deposition (CVD). The MOFs crystal deposition was optimised varying the intial conditions of ZIF-8 synthesis. Results: To evaluate the correctc synthesis of the compound, the films were charactised by Fourier Transformed Infrared Spectroscopy (FT-IR), grazing-angle XRD and Scanning Electron Microscopy (SEM). An optimisation of synthesis was successfully reached. XRD results show that the compound is crystalline and corresponds to a ZIF-8 phase. IR results also confirm the correct formation of ZIF-8 and SEM images allow see that the compound grew between the columns. The compound appears to have a catalytic activity however the experiments still continue. Conclusions: The compound is successfully deposited and synthesis was optimised. It has crystalline structure, grew between the columns and it corresponds to ZIF-8. Catalysis results are not still conclusive but sensations are positive